Measuring pulmonary gas exchange using compartment‐selective xenon‐polarization transfer contrast (XTC) MRI. Issue 5 (7th December 2020) - Amzajerdian, Faraz; Ruppert, Kai; Hamedani, Hooman; Baron, Ryan; Xin, Yi; Loza, Luis; Achekzai, Tahmina; Duncan, Ian F.; Qian, Yiwen; Pourfathi, Mehrdad; Kadlecek, Stephen; Rizi, Rahim R.
Abstract : Purpose: To demonstrate the feasibility of generating red blood cell (RBC) and tissue/plasma (TP)‐specific gas‐phase (GP) depolarization maps using xenon‐polarization transfer contrast (XTC) MR imaging. Methods: Imaging was performed in three healthy subjects, an asymptomatic smoker, and a chronic obstructive pulmonary disease (COPD) patient. Single‐breath XTC data were acquired through a series of three GP images using a 2D multi‐slice GRE during a 12 s breath‐hold. A series of 8 ms Gaussian inversion pulses spaced 30 ms apart were applied in‐between the images to quantify the exchange between the GP and dissolved‐phase (DP) compartments. Inversion pulses were either centered on‐resonance to generate contrast, or off‐resonance to correct for other sources of signal loss. For an alternative scheme, inversions of both RBC and TP resonances were inserted in lieu of off‐resonance pulses. Finally, this technique was extended to a multi‐breath protocol consistent with tidal breathing, involving 30 consecutive acquisitions. Results: Inversion pulses shifted off‐resonance by 20 ppm to mimic the distance between the RBC and TP resonances demonstrated selectivity, and initial GP depolarization maps illustrated stark magnitude and distribution differences between healthy and diseased subjects that were consistent with traditional approaches. Conclusion: The proposed DP‐compartment selective XTC MRI technique provides information on gas exchange between all three detectable states of xenon in the lungs and is sufficiently sensitive to indicate differences in lung function between the study subjects. Investigated extensions of this approach to imaging schemes that either minimize breath‐hold duration or the overall number of breath‐holds open avenues for future research to improve measurement accuracy and patient comfort.